ANALISIS MUTU BEBAN KINERJA DOSEN BIDANG PENELITIAN BERBASIS KNOWLEDGE CONVERSION - Eka eka (UHN IGB Sugriwa Denpasar, 2022)
Lecturers are scientists and disseminators of knowledge in education so that lecturers not only teach but also conduct research. Lecturer performance can be measured through the Performance Load of Higher Education Lecturers of each agency so that the achievement of lecturer performance can be measured. The purpose of this research is to describe the information and knowledge of BKD in the research field. The method used is 5C converted to 3C. The 5C method is contextualized, categorized, calculated, corrected, and condensed. The next conversion process to obtain knowledge is carried out using the 4C method, namely comparison, consequences, connection. The results of the study can be concluded that the research performance of lecturers is divided into 3 clusters, namely lecturers with additional assignments, ordinary lecturers and professors. The result is that there are several clusters of publications that have not been carried out by several lecturers, especially lecturers with additional (structural) assignments and several professor's obligations that need to be optimized again in one semester in order to obtain optimal lecturer performance so that they are headed for a superior money research university in accordance with the university's vision.